Character, Resilience, and Critical Thinking of Biology Students after the Covid-19 Pandemic: How They are Correlated - Asham Bin Jamaluddin; Andi Citra Pratiwi; Ifa Safira; Nurdiyanti Nurdiyanti (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a correlational study which aims to determine the relationship between character and resilience; character and critical thinking; resilience and critical thinking; and the character, resilience, and critical thinking of undergraduate biology students after the Covid-19 pandemic. The research population is all undergraduate students majoring in Biology and Science Education at Makassar State University, Makassar Muhammadiyah University and Bosowa University who are enrolled in the 2nd semester of the 2021-2022 academic year. The research sample consisted of 3 classes with a total of 120 students who were selected through cluster random sampling technique. The data of students’ character and resilience were obtained using questionnaire techniques, while data on students’ critical thinking skills were obtained by using an essay test on General Biology subject. The results of data analysis showed a correlation between character and resilience (p=0.000); character and critical thinking (p=0.000); character and critical thinking (p=0.000); student character, resilience and critical thinking (p=0.000). The finding of this study suggest that the correlation appears due to the potential of character and resilience to influence, empower, and enhance students’ critical thinking skills